Cover Picture: Nanoantidote for repression of acidosis pH promoting COVID‐19 infection (View 4/2022). Issue 4 (25th July 2022) - Liu, Qidong; Ruan, Huitong; Sheng, Zhihao; Sun, Xiaoru; Li, Siguang; Cui, Wenguo; Li, Cheng
Abstract : Acidosis‐related pH promotes SARS‐CoV‐2 pseudovirus infection by increasing cell membrane ACE2 expression. A CaCO3‐NPs antacid nanoantidote restored the normal blood related pH 7.4, attenuating the SARS‐CoV‐2 pseudovirus infection. In article number 20220004, Wenguo Cui, Cheng Li, Siguang Li and their co‐workers have suggested the existence of a positive feedback loop in which SARS‐CoV‐2 infection‐induced acidosis enhances further SARS‐CoV‐2 infection. CaCO3‐NPs nanoantidote may become an effective antacid.